International Platform on Sport & Development!
This is the new version of the International Platform on Sport & Development. The International Platform on Sport & Development (the `Platform`) is a website entirely dedicated to the thematic field of Sport & Development. It was initiated after the first International Conference on Sport and Development was held in Magglingen, Switzerland in 2003.